IDENTIFIKASI PERILAKU CYBERBULLYING DI SEKOLAH SEBAGAI UPAYA PREVENTIF - Fitria Yola; Lisa Sis Mona; Masril Masril (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Cyberbullying is currently rampant, making it an important reason for teachers and guidance counselors to address this problem in students. The purpose of this study was to identify cyberbullying behavior and preventive efforts in students. The results of the study showed that cyberbullying in the school environment occurs in various forms, including verbal insults, spreading rumors or personal information, as well as online threats, teasing, and derogatory sarcasm. Prevention efforts currently implemented in several schools, such as awareness programs and anti-cyberbullying policies. Prevention includes the development of more intensive education programs on cyberbullying, involving students, teachers, and parents. The impacts experienced by students who experience bullying include: withdrawing from the environment, lack of self-confidence and even choosing not to come to school.